Active binding sites for ofloxacin resulted from adsorptive fractionation of humic acid on kaolinite. (1st January 2023) - Ma, Cuiyan; Bi, Erping
Abstract: The adsorptive fractionation of humic acid (HA) at the interface between minerals and water can significantly affect the fate of pollutants in water-soil environment. However, the adsorptive fractionation behavior of HA on kaolinite and its effect on the migration of fluoroquinolones (FQs) have not been fully understood. In this study, fluorescence and infrared spectroscopy, combined with two-dimensional correlation analyses, were used to explore the adsorptive fractionation of humic acid (HA) and its effects on ofloxacin adsorption on kaolinite. The results indicated that humic-like, rather than reduced quinone-like and tyrosine-like, was the main adsorptive fractionation component and preferentially bound to the Al–O sites of kaolinite. The adsorption mechanisms of humic-like and tyrosine-like mainly include hydrogen bonds between acidic functional groups and the Si–O or Al–O groups of kaolinite, n-π electron donor-acceptor interaction and electrostatic attraction. At pH 7.0, with addition of 4.0 and 16.0 mg C/L HA in solution, the adsorptive fractionation of HA on kaolinite led to increases in ofloxacin (in zwitterionic form) adsorption capacity by 1.46 and 3.35 mg/g, respectively. The interactions between ofloxacin and the humic-like were mainly hydrogen bonds and electrostatic attraction. Therefore, the influence of adsorptive fractionation of dissolved organic matter on minerals should be considered in estimating FQs environmental behaviors. Graphical abstract: Image 1 Highlights: Adsorptive fractionation of humic acid (HA) on kaolinite was observed. Adsorption affinity order was humic-like > tyrosine-like > reduced quinone-like. Binding of HA with aluminol was stronger than that of siloxane in kaolinite. HA adsorptive fractionation increased the sorption of ofloxacin on kaolinite. Ofloxacin primarily adsorbed to sites of humic-like loaded on kaolinite.